Dynamic maths interviews to identify educational needs of students showing low math achievement. Issue 3 (4th May 2022) - Kaskens, J.; Goei, S. L.; Van Luit, J. E. H.; Verhoeven, L.; Segers, E.
ABSTRACT: We investigated the adequacy of the conduct and possible benefits of the use of dynamic maths interviews by 19 fourth grade teachers with students showing low maths achievement to facilitate the identification of maths needs. This study shows the potential of an analytical framework to evaluate the adequacy and benefits of dynamic maths interviews in a more valid way by viewing relevant aspects in conjunction. The intervention consisted of a dynamic maths interview teacher professional development programme and a practice period. During this practice period the teachers conducted an interview with each individual student involved in this study. Qualitative analyses of the transcripts of the video-recorded interviews showed the conduct of the individual dynamic maths interviews to be adequate and to facilitate the identification and understanding of the educational needs of students with low maths achievement. Using dynamic maths interviews, teachers provided feedback and support that were clearly attuned to the specific maths needs of students.